2016
DOI: 10.1120/jacmp.v17i4.5965
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the normalized prescription isodose line on the magnitude of Monte Carlo vs. pencil beam target dose differences for lung stereotactic body radiotherapy

Abstract: In lung stereotactic body radiotherapy (SBRT) cases, the pencil beam (PB) dose calculation algorithm is known to overestimate target dose as compared to the more accurate Monte Carlo (MC) algorithm. We investigated whether changing the normalized prescription isodose line affected the magnitude of MC vs. PB target dose differences. Forty‐eight patient plans and twenty virtual‐tumor phantom plans were studied. For patient plans, four alternative plans prescribed to 60%, 70%, 80%, and 90% isodose lines were each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
(41 reference statements)
0
16
0
Order By: Relevance
“…In this work, we have investigated only the low‐density range for clinical energies of interest in the small field sizes, due to inherent limitations of the 3'D printing fabrication process employed. That said, the investigation of small field size and low‐density tissue range for AXB validation is of clinical relevance as these conditions are akin to those of lung SBRT treatments, which has been a topic of interest with respect to the application of AXB 21, 22, 23, 24, 25…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we have investigated only the low‐density range for clinical energies of interest in the small field sizes, due to inherent limitations of the 3'D printing fabrication process employed. That said, the investigation of small field size and low‐density tissue range for AXB validation is of clinical relevance as these conditions are akin to those of lung SBRT treatments, which has been a topic of interest with respect to the application of AXB 21, 22, 23, 24, 25…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23] Moreover, the magnitude of the dose error varies widely from case to case, and can depend on a multitude of factors. [23][24][25][26][27] Interestingly, in a phantom study, 25 Aarup et al found that the difference in calculated target dose between MC and PBC algorithms depends systematically on the density of the surrounding lung tissue. Specifically, they compared dose calculation using different algorithms on a spherical "target" surrounded by simulated "lung" tissue of different densities.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, our study used DCA as the conformal technique for comparison. While DCA is a popular conformal technique used for lung SBRT, 9,10,[14][15][16] other techniques are also used such as multiple noncoplanar conformal beams.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] The obstacle of dose calculation has been addressed by the development of more accurate dose calculation algorithms in commercial treatment planning systems, from earlier homogeneous dose calculations to newer dose algorithms incorporating heterogeneity correction. 4 These latter algorithms are usually categorized from Type A to Type C, with increasing dose calculation accuracies: 8,9 (1) Type A: algorithms with a one-dimensional equivalent path length correction such as pencil beam (PB) convolution and ray tracing; 5,7,10 (2) Type B: algorithms applying two-dimensional corrections such as collapsed cone convolution (CCC) 11 and analytical anisotropic algorithm (AAA); 12 and (3) Type C: advanced algorithms such as fast Monte Carlo algorithms 4,13 and Boltzmann Solver-based algorithms such as acuros external beam (AXB). 9 Dose calculation has been widely compared among the above algorithms for lung SBRT, with interalgorithm differences mostly observed for the target dose.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation